2016
DOI: 10.1021/acs.orglett.6b00929
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder Reactions of Furans with Itaconic Anhydride: Overcoming Unfavorable Thermodynamics

Abstract: Unfavorable thermodynamics often render furans reluctant to engage in high-yielding Diels-Alder (DA) cycloaddition reactions. Here we report the highly efficient conversion of the bio-sourced reactants itaconic anhydride (IA) and furfuryl alcohol (FA) to a single DA adduct. The free energy advantages provided by anhydride ring-opening and crystal lattice energy of the product overcome the loss of aromaticity of the furanoid diene. Detailed 1H NMR studies provided valuable insights about relevant kinetic and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 24 publications
3
41
2
Order By: Relevance
“…This has been recently illustrated by Bai et al where polymers were prepared, albeit slowly ( t > 24 h), by the ROMP of tricyclic endo , exo ‐functional DA adducts, derived from furfuryl alcohol and itaconic anhydride. An in‐depth mechanistic study of the formation of these tricyclic adducts via tandem Diels–Alder cycloaddition and lactonization has been recently reported by Pehere et al…”
Section: Introductionmentioning
confidence: 99%
“…This has been recently illustrated by Bai et al where polymers were prepared, albeit slowly ( t > 24 h), by the ROMP of tricyclic endo , exo ‐functional DA adducts, derived from furfuryl alcohol and itaconic anhydride. An in‐depth mechanistic study of the formation of these tricyclic adducts via tandem Diels–Alder cycloaddition and lactonization has been recently reported by Pehere et al…”
Section: Introductionmentioning
confidence: 99%
“…This observation was also reported independently and simultaneously by Hoye et al who were investigating the Diels-Alder addition of itaconic anhydride 6 to a range of furans. 27 Compound 7 is formed as a result of a tandem Diels-Alder cycloaddition and lactone formation, with the product crystallising from solution, or from the neat reaction mixture. It is believed that the Diels-Alder addition occurs rapidly and reversibly, as is typical of Diels-Alder additions to furans, 28,29,30 and that the second step is lactone formation, with the overall reaction being driven by the crystallisation of polycyclic oxanorbornene carboxylic acid 7.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In recent work, we were able to demonstrate that the reaction between itaconic anhydride 6 and furfuryl alcohol 4 proceeded cleanlya tr oom temperature to give acid 8 by ao ne-pot and 100 %a tom-economical tandem Diels-Alderlactone formation process requiringn oa dditional reagents, catalysts or solvents (Scheme1). [12] We also demonstrated that av ariety of esters and amides of acid 8 are good substrates for ring-openingm etathesis polymerization (ROMP) when using Grubbs second-generation catalyst 9.T he polymerizations displayed aw ell-controlled linear relationship between polymer molecular weight and monomer/catalyst ratio and were able to produce both random andb lock copolymers. [12] We also demonstrated that av ariety of esters and amides of acid 8 are good substrates for ring-openingm etathesis polymerization (ROMP) when using Grubbs second-generation catalyst 9.T he polymerizations displayed aw ell-controlled linear relationship between polymer molecular weight and monomer/catalyst ratio and were able to produce both random andb lock copolymers.…”
Section: Introductionmentioning
confidence: 79%
“…[11] The same result was obtained independently and simultaneously by the group of Hoye. [12] We also demonstrated that av ariety of esters and amides of acid 8 are good substrates for ring-openingm etathesis polymerization (ROMP) when using Grubbs second-generation catalyst 9.T he polymerizations displayed aw ell-controlled linear relationship between polymer molecular weight and monomer/catalyst ratio and were able to produce both random andb lock copolymers. [13] However,t he polymerization of these monomers was very slow,w ith at ypical reaction taking 72 ht or each completion.T his limited the variety of polymer architectures that could be produced as "dead"c hain ends become as ignificant problem over extended polymeri-Well-controlled and extremelyr apid ring-opening metathesis polymerization of unusualo xanorbornene lactam esters by Grubbs third-generation catalysti su sed to preparearange of bio-based homo-a nd copolymers.…”
Section: Introductionmentioning
confidence: 79%